First-year estimated glomerular filtration rate variability after pre-end-stage renal disease program enrollment and adverse outcomes of chronic kidney disease. Issue 12 (5th July 2018) - Tsai, Ching-Wei; Huang, Han-Chun; Chiang, Hsiu-Yin; Chung, Chih-Wei; Chiu, Hsien-Tsai; Liang, Chih-Chia; Yu, Tsung; Kuo, Chin-Chi
Abstract: Background: Scarce evidence associates the first-year estimated glomerular filtration rate (eGFR) variability and longitudinal change scales concomitantly to the risk of developing end-stage renal disease (ESRD), acute coronary syndrome (ACS) and death following pre-ESRD program enrollment in chronic kidney disease (CKD). Methods: We conducted a prospective cohort study of 5092 CKD patients receiving multidisciplinary care between 2003 and 2015 with careful ascertainment of ESRD, ACS and death during the follow-up. First-year eGFR variability and longitudinal change scales that were based on all first-year eGFR measurements included coefficient of variation of eGFR (eGFR-CV), percent change (eGFR-PC), absolute difference (eGFR-AD), slope (eGFR-slope) and area under the curve (AUC). Results: A total of 786 incident ESRD, 292 ACS and 410 death events occurred during the follow-up. In the multiple Cox regression, the fully adjusted hazard ratios (HRs) of progression to ESRD for each unit change in eGFR-CV, eGFR-PC, eGFR-AD, eGFR-slope, eGFR-AUC were 1.03 [95% confidence interval (CI) 1.02–1.04], 1.04 (1.03–1.04), 1.16 (1.14–1.18), 1.16 (1.14–1.17) and 1.04 (1.03–1.04), respectively. The adjusted HRs for incident ESRD comparing the extreme with the reference quartiles of eGFR-CV, eGFR-PC, eGFR-AD, eGFR-slope and eGFR-AUC were 2.67 (95% CI 2.11–3.38), 8.34 (6.33–10.98), 19.08 (11.89–30.62), 13.08 (8.32–20.55) and 6.35 (4.96–8.13), respectively. Similar direction of the effects on the risk of developing ACS and mortality was observed. In the 2 × 2 risk matrices, patients with the highest quartile of eGFR-CV and concomitantly with the most severely declining quartiles of any other longitudinal eGFR change scale had the highest risk of all outcomes. Conclusions: The dynamics of eGFR changes, both overall variability and longitudinal changes, over the first year following pre-ESRD program enrollment are crucial prognostic factors for the risk of progression to ESRD, ACS and deaths among patients with CKD. A risk matrix combining the first-year eGFR variability and longitudinal change scales following pre-ESRD enrollment is a novel approach for risk characterization in CKD care. Randomized trials in CKD may be required to ascertain comparable baseline eGFR dynamics.